PERBANDINGAN SERVICE QUALITY MUSEUM KRETEK DENGAN MUSEUM JENANG KUDUS - Asyharudin Hanif; Ihfadz Lucky Alfa Saputra Lucky Alfa Saputra; Dewi Putri Mardiana Putri Mardiana; Rangga Primadasa (Journal of Industrial Engineering and Technology, 2020)
In Kudus district, has two museums which Museum Kretek and Museum Jenang Kudus. In 2018 the number of visitors to the Museum Kretek reached 102,998 visitors, while the total visitors to the Musuem Jenang Kudus reached 397,625. The difference reaching  294,627 raises the question of how the service quality between the two museums. This study used the SERVQUAL Model method to determine the service quality of the two Musuem as well as a comparison of the service quality of the Museum Kretek and the Museum Jenang Kudus. The results of the study revealed that of the 100 reapondents who had visited the Museum Kretek and the Museum Jenang Kudus, the Museum Jenang Kudus had a better perception of service quality according to respondents. Based on the results of this study, we suggest that both museums improve service quality, especially in service quality items that get a low perception of respondents